False Needs in the Digital Age: The Role of Social Media in Junk Food Cravings - Mainali, Sujit; Neupane, Kamal; Chuwan, Nar Kumar; Pandey, Gaurav (Journal of Productive Discourse, 2025)
Social media (SM) has emerged as an influential marketing tool shaping the junk food (JF) consumption behavior of teenage students. This article aims to explore the role SM plays in influencing the JF consumption behaviors of teenage students in Kathmandu Metropolitan City (KMC). The study adopts a mixed-methods approach, using an explanatory sequential research design. Following this design, a cross-sectional survey (199 respondents) was conducted, and its significant findings were further explained through qualitative data collected via a focus group discussion (FGD) (10 participants). Both phases of the study were conducted among students of grades 11 and 12 at Madan Bhandari Memorial Secondary School, located in KMC. The study found that teenage students frequently consume JF. Although most of them consider its consumption unnecessary, they continue to consume it frequently, indicating a gap between their understanding and behavior. Similarly, SM platforms offering video content, such as YouTube, Facebook, and Instagram, were found to be more engaging for the students. A substantial number of students were active on SM, with nearly two-thirds of respondents using it for 1–3 hours daily. The study revealed a significant relationship between the use of SM—particularly engagement with short video content—and the consumption of JF. These findings affirm the role of media in creating false needs, as envisioned by the critical theorist Herbert Marcuse.